2020
DOI: 10.1111/1471-0528.16597
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord clamping and skin‐to‐skin contact in deliveries from women positive for SARS‐CoV‐2: a prospective observational study

Abstract: Objective To demonstrate that delayed cord clamping (DCC) is safe in mothers with confirmed SARS-CoV-2 infection. Design, setting and participants Prospective observational study involving epidemiological information from 403 pregnant women with SARS-CoV-2 between 1 March and 31 May 2020. Data were collected from 70 centres that participate in the Spanish Registry of COVID-19. Methods Patients' information was collected from their medical chart. Main outcomes and measures The rate of perinatal transmission of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 18 publications
0
17
0
2
Order By: Relevance
“…During the first weeks of the first wave of the pandemic, and as consequence of the lack of evidence regarding the possibility of contagion during the practice of post-delivery skin-to-skin contact, it was recommended that, after birth, newborns should be immediately separated from their mothers (Griffin et al, 2020;Yang et al, 2020). However, as the transmission mechanism of COVID-19 became better known, it was determined that maintaining certain preventive measures, for example, the use of a mask by the mother, or hand hygiene, did not increase the risk of horizontal transmission during the practice of immediate skin-to-skin contact (Mejía et al, 2021;Salvatore et al, 2020;Sánchez-Luna et al, 2021). Nevertheless, implementation of international recommendations to recover this practice have not been homogeneous across all countries or even in all hospital centers (Lavizzari et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…During the first weeks of the first wave of the pandemic, and as consequence of the lack of evidence regarding the possibility of contagion during the practice of post-delivery skin-to-skin contact, it was recommended that, after birth, newborns should be immediately separated from their mothers (Griffin et al, 2020;Yang et al, 2020). However, as the transmission mechanism of COVID-19 became better known, it was determined that maintaining certain preventive measures, for example, the use of a mask by the mother, or hand hygiene, did not increase the risk of horizontal transmission during the practice of immediate skin-to-skin contact (Mejía et al, 2021;Salvatore et al, 2020;Sánchez-Luna et al, 2021). Nevertheless, implementation of international recommendations to recover this practice have not been homogeneous across all countries or even in all hospital centers (Lavizzari et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we did not consider the additional impact of initiating KMC before stabilisation [38] , [39] , [40] or implementation at a community-level [41] . Hence these estimates might underestimate the potential magnitude of these benefits and also other evidence-based newborn care practices, such as delayed cord clamping [42] . Additional studies are underway to provide more precise evidence on SARS-CoV-2 transmission from mother to newborn [43] .…”
Section: Discussionmentioning
confidence: 99%
“…[66][67][68] A prospective observational study of pregnant women with SARS-CoV-2 demonstrated that compared with early cord clamping (less than 30 seconds; n5231), delayed cord clamping (more than 30 seconds; n5172) was not associated with significant differences in positive neonatal test results for SARS-CoV-2 infection; no confirmed vertical transmission cases were detected. 69 Anti-SARS CoV-2 immunoglobulin G antibodies are detected in umbilical cord blood of neonates born to mothers who received coronavirus disease 2019 (COVID-19) mRNA vaccines during pregnancy. [70][71][72] Placental transfusion may enhance passive immunity in the neonate, but there are not studies to date to confirm this possibility.…”
Section: Maternal Severe Acute Respiratory Syndrome Coronavirus 2 (Sa...mentioning
confidence: 99%